AKIBAT HUKUM AHLI WARIS YANG MENOLAK MENANGGUNG HUTANG PEWARIS YANG MELEBIHI HARTA WARISAN: KAJIAN HUKUM PERDATA DAN HUKUM ISLAM - Bagus Prayitno; Dian Septiandani; Dharu Triasih (Semarang Law Review (SLR), 2025)
There are several types of events or legal events that are essential for humans in their lives, including the legal events of birth, the event of marriage, and the legal event of death. One aspect that arises after death is the obligation of the heirs to the debts of the testator. According to civil law (KUH Perdata), all inherited assets, including the debts of the testator, are the responsibility of the heirs. The heirs have the option to accept the inheritance in full, accept it with conditions (beneficiaire aanvaarding), or reject the inheritance. If the heirs choose to reject the inheritance, they are not responsible for paying the debts of the testator. Meanwhile, in Islamic law, inheritance is calculated after deducting the debts of the testator, the costs of managing the corpse, and the will. The heirs are only responsible for paying debts according to the value of the inheritance received and do not need to bear debts that exceed the value of the inheritance. The main difference between the two legal systems is the protection given to the heirs; civil law tends to be stricter, while Islamic law offers more protection to the heirs from obligations that exceed the value of the inheritance. Chapter 1 of this study discusses the background of the problems that arise due to death, often causing disputes regarding the obligation to pay debts. Chapter 2 explains the concept of inheritance law in the Civil Code and Islamic law, identifying the main elements of inheritance and the responsibilities of heirs in both systems. Chapter 3 outlines the research methodology that uses normative and analytical descriptive approaches for the comparison of legal systems. Chapter 4 presents the results of the research and analysis on the legal implications for heirs who refuse to bear the debts of the testator in the context of both legal systems. This research is expected to provide in-depth insight into the rights and obligations of heirs, as well as assist policy makers in formulating fair regulations.   Abstrak Ada beberapa macam kejadian atau peristiwa hukum yang esensil untuk manusia dalam kehidupannya, meliputi peristiwa hukum kelahiran, kejadian adanya perkawinan, dan peristiwa hukum kematian. Salah satu aspek yang muncul setelah kematian adalah kewajiban ahli waris terhadap hutang pewaris. Menurut hukum perdata (KUH Perdata), seluruh harta peninggalan, termasuk hutang-hutang pewaris, menjadi tanggungan ahli waris. Ahli waris memiliki opsi untuk menerima warisan secara penuh, menerima dengan syarat (beneficiaire aanvaarding), atau menolak warisan. Jika ahli waris memilih untuk menolak warisan, mereka tidak bertanggung jawab atas pembayaran hutang pewaris. Sementara itu, dalam hukum Islam, warisan dihitung setelah mengurangi hutang pewaris, biaya pengurusan jenazah, dan wasiat. Ahli waris hanya bertanggung jawab untuk membayar hutang sesuai dengan nilai warisan yang diterima dan tidak perlu menanggung hutang yang melebihi nilai harta warisan. Perbedaan utama antara kedua sistem hukum ini adalah perlindungan yang diberikan kepada ahli waris; hukum perdata cenderung lebih ketat, sedangkan hukum Islam menawarkan perlindungan lebih terhadap ahli waris dari kewajiban yang melebihi nilai warisan. Bab 1 dari penelitian ini membahas latar belakang masalah yang muncul akibat kematian, seringkali menyebabkan perselisihan terkait kewajiban membayar hutang. Bab 2 menjelaskan konsep hukum waris dalam KUH Perdata dan hukum Islam, mengidentifikasi elemen utama dari pewarisan dan tanggung jawab ahli waris dalam kedua sistem tersebut. Bab 3 menguraikan metodologi penelitian yang menggunakan pendekatan normatif dan deskriptif analitis untuk perbandingan sistem hukum. Bab 4 menyajikan hasil penelitian dan analisis mengenai implikasi hukum bagi ahli waris yang menolak menanggung hutang pewaris dalam konteks kedua sistem hukum. Penelitian ini diharapkan memberikan wawasan mendalam mengenai hak dan kewajiban ahli waris, serta membantu pembuat kebijakan dalam merumuskan regulasi yang adil.